The hidden palace - Wecker, Helene ([Golem and the jinni, 2021)
Pretending to be human, magical beings Chava, a golem, and Ahmad, a jinni, find their lives intertwined as they try to make sense of the world around them and the people whose lives they have unwittingly affected.